‘Il filo di Arianna’: La stanza del figlio and the Healing Value of Nanni Moretti’s Cinema of Poetry - Riccobono, Rossella (Spunti e Ricerche, 2016)
In this essay Nanni Moretti’s La stanza del figlio (2001) is studied through the deployment of symbols belonging to several artistic languages. By interpreting the references made by Moretti in La stanza del figlio to Raymond Carver’s poetry and to Brian Eno’s song ‘By this river’, and by adopting the concept of ‘cinema of poetry’ as conceived by Pier Paolo Pasolini, this study will introduce the image of the river and its elements of horizontality and linearity to the poetics of Moretti’s cinema. This will enable us to better evince the possibility of poetry and its healing effects within his cinematic language and, fundamentally, to assist in reading La stanza del figlio in an original way.